A Diesel Engine Model Including Exhaust Flap, Intake Throttle, LP-EGR and VGT. Part II: Identification and Validation. Issue 15 (2015) - Stürzebecher, Christoph; Reß, Johannes; Bohn, Christian; Märzke, Frank; Frase, Robert
Abstract: For identifying a mean-value model of a diesel engine measurements were taken on a four cylinder diesel engine. The optimization problems are solved using a least-squares algorithm. The static and dynamic validation of the model confirms the suitability of the developed model. The model is able to describe the dynamic behavior of the engine correctly, for example the non-minimum phase behavior in the pressure dynamic. The mean absolute relative error of all measured variables is about 2%.